Application of the Copenhagen Soccer Test in high-level women players - locomotor activities, physiological response and sprint performance - Bendiksen, M.; Pettersen, S. A.; Ingebrigtsen, J.; Randers, M. B.; Brito, J.; Mohr, M.; Bangsbo, J.; Krustrup, P. (Human Movement Science, 2013)
We evaluated the physiological response, sprint performance and technical ability in various phases of the Copenhagen Soccer Test for Women (CSTw) and investigated whether the locomotor activities of the CSTw were comparable to competitive match-play (CM). Physiological measurements and physical/technical assessments were performed during CSTw for eleven Norwegian high-level women soccer players. The activity pattern during CSTw and CM was monitored using the ZXY tracking system. No differences were observed between CSTw and CM with regards to total distance covered (10093 ± 94 and 9674 ± 191 m), high intensity running (1278 ± 67 and 1193 ± 115 m) or sprinting (422 ± 55 and 372 ± 46 m) (p > .05). During CSTw, average HR was 85 ± 2%HRmax with 35 ± 2% playing time >90%HRmax. Blood lactate increased (p < .05) from 1.4 ± 0.3 mM at rest to an average of 4.7 ± 0.5 mM during CSTw, with no changes during the test. Blood glucose was 5.4 ± 0.3 mM at rest and remained unaltered during CSTw. Sprint performance (2 × 20 m) decreased (p < .05) by 3% during CSTw (8.19 ± 0.06-8.47 ± 0.10 s). In conclusion, the locomotor activities during CSTw were comparable to that of high-level competitive match-play. The physiological demands of the CSTw were high, with no changes in heart rate, blood lactate or technical performance during the test, but a lowered sprint performance towards the end of the test.